2011
DOI: 10.1186/1472-6920-11-93
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of medical students to medical leadership and management: a systematic review to inform curriculum development

Abstract: BackgroundThere is a growing acknowledgement that doctors need to develop leadership and management competences to become more actively involved in the planning, delivery and transformation of patient services. We undertook a systematic review of what is known concerning the knowledge, skills and attitudes of medical students regarding leadership and management. Here we report the results pertaining to the attitudes of students to provide evidence to inform curriculum development in this developing field of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 21 publications
7
85
0
5
Order By: Relevance
“…When comparing our results to the results of other studies, we were able to conrm that students understand the clinical competences of family doctors (8), but fail to understand some other competences of family doctors (7,(9)(10)(11). In a qualitative research synthesis about medical students' perception of and attitudes towards family medicine, it was found that most of the included studies describe factors which inuence a career choice for family medicine (24).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…When comparing our results to the results of other studies, we were able to conrm that students understand the clinical competences of family doctors (8), but fail to understand some other competences of family doctors (7,(9)(10)(11). In a qualitative research synthesis about medical students' perception of and attitudes towards family medicine, it was found that most of the included studies describe factors which inuence a career choice for family medicine (24).…”
Section: Discussionmentioning
confidence: 57%
“…We could add that students also recognise the importance of organisational and management skills of family doctors and recognise them as teachers in organisational and management skills. In a systematic review it was found that students recognised the need to develop leadership and management competences, since relatively little emphasis was placed on leadership and management in medical curricula (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of management skills is becoming crucial for dentists to manage their practices successfully (Dunning, & Tacha, 2011;Willis, 2009). These skills are often neglected in faculty curriculum plan despite tendencies that students recognize them as crucial (Abbas, & Benson, 2011;Kalenderian, & Timothé, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators from programs in dentistry, [58][59][60][61] medicine, 62,63 and physical therapy 64 have conducted surveys and interviews of students, academic administrators, faculty members, practitioners, and alumni to determine the need for teaching SLD and perceptions on the best approach to teaching it.…”
Section: Student Leadership Development In Health Professions Educationmentioning
confidence: 99%